Methotrexate in the treatment of atopic dermatitis - Nowicki, Roman; Grubska-Suchanek, Elżbieta; Wilkowska, Aleksandra; Khvorik, Dmitrij F.; Trzeciak, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
Atopic dermatitis (AD) is a common inflammatory skin disease. Most cases start in children although some have been reported in adults. Moderate to severe cases of AD not responding to topical treatments may need systemic therapy. Methotrexate may be considered in patients with severe AD who did not achieve the expected improvement after cyclosporine, or who had adverse effects and no possibility of biological treatment with monoclonal antibodies or Janus kinase inhibitors.